Development of the Geo-Food Board Game to Improve Geometry Skills Based on Van Hiele’s Levels of Thinking in Fourth Grade Elementary Students - Laurencia Lucia Rosok Klau Muti; Dani Kusuma (Electronic Journal of Education, Social Economics and Technology, 2025)
The lack of interactive learning media in mathematics education, particularly in geometry, often makes it difficult for students to understand the material and leads to boredom during learning. Therefore, there is a need for game-based media that engages students and encourages active participation in classroom learning. This study aims to examine the development process, validity, effectiveness, and practicality of the "GEO-Food" board game in improving geometry skills based on Van Hiele’s levels of thinking in fourth-grade elementary students. This research is a type of Research and Development (RD) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through expert validation questionnaires, teacher and student response questionnaires, and pre-test and post-test on quadrilateral material. The trial results showed that the media validity score was 100% by media experts and 96% by material experts, both categorized as "very valid." The media was considered moderately effective, with an N-Gain score of 70.73%, and an average score increase from 38.07% (pre-test) to 80.67% (post-test). The practicality of the media was rated at 93% by teachers and 88% by students, both categorized as "very practical." It can be concluded that the "GEO-Food" board game is valid, effective, and practical for improving geometry skills based on Van Hiele’s levels of thinking in fourth-grade elementary students.